Electrospinning Techniques: Electrospinning‐Based Strategies for Battery Materials (Adv. Energy Mater. 2/2021). Issue 2 (14th January 2021) - Li, Xiaoyan; Chen, Weichen; Qian, Qingrong; Huang, Haitao; Chen, Yuming; Wang, Ziqiang; Chen, Qinghua; Yang, Jing; Li, Ju; Mai, Yiu‐Wing
Abstract : In article number 2000845 Yuming Chen, Ziqiang Wang, Qinghua Chen, Jing Yang, Ju Li, Yiu‐Wing Mai and co‐workers review electrospinning‐based strategies for battery materials. The combination of electrospinning techniques with other materials processing techniques is a powerful synthesis strategy that can tailor the structural and compositional features of electrode materials for energy storage applications. The synthesized nanomaterials can also work as nanoreactors for in situ transmission electron microscopy characterization, that enables an understanding of the mechanisms of the materials synthesis process and electrochemical reaction behavior.